Integrasi Psikologi Agama Dalam Membentuk Karakter Islami Pada Generasi Muda - Faqih Muhammad Barraq; Hafizh Fadhilur Rohman; Yuminah Rahmatullah (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
Islamic character in the youth is significantly influenced by various factors, Including religious education and their psychological understanding of Islamic teachings. This study aims to explore how the psychology of religion plays a role in the formation of Islamic character in the youth of Indonesia. In this study, the psychology of religion is understood as the science that examines the impact of religion on an individual's psychological development, including in the aspects of morality and ethics. The formation of Islamic character in the youth can be carried out through an integrative approach, combining the principles of psychology with Islamic values. This research uses a qualitative approach by analyzing literature and case studies related to the psychology of religion and Islamic education in Indonesia. The results of the study indicate that the application of psychology of religion in education can form a strong Islamic character by instilling moral values in accordance with Islamic teachings, such as honesty, discipline, and empathy.